1982
DOI: 10.1056/nejm198207153070302
|View full text |Cite
|
Sign up to set email alerts
|

Antigen-Specific Suppressor T Lymphocytes in Human Lymphatic Filariasis

Abstract: Immune responses to parasite antigens are much lower in patients with microfilaremia than in persons with other manifestations of brugian filariasis. To determine whether hyporeactivity is associated with changes in populations of lymphocytes that regulate immune responses, we quantitated helper and suppressor T cells in the blood of patients infected with Brugia malayi. Increased numbers of suppressor T cells were present in 15 of 17 patients with microfilaremia and in six of 11 patients with elephantiasis. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0
1

Year Published

1985
1985
2010
2010

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(34 citation statements)
references
References 22 publications
4
29
0
1
Order By: Relevance
“…Previous studies in patients with brugian filanasis have suggested active suppression by either monocytes (8) or suppressor CD8+ T lymphocytes (7). Similar studies with PBMC from persons with Wuchereria bancrofti infection have failed to identify such suppressor cell populations ( 11,14).…”
Section: Introductionmentioning
confidence: 71%
“…Previous studies in patients with brugian filanasis have suggested active suppression by either monocytes (8) or suppressor CD8+ T lymphocytes (7). Similar studies with PBMC from persons with Wuchereria bancrofti infection have failed to identify such suppressor cell populations ( 11,14).…”
Section: Introductionmentioning
confidence: 71%
“…The reasons for the lower antibody titers to this specific antigen in the microfilaremic subjects are not known. Immunoregulatory processes that develop in the course of chronic infection, such as suppression of T and B cell responses to filarial antigens and development ofimmune complexes may, in part, be responsible (2)(3)(4)39). In addition, it is possible that the isotype of antifilarial antibodies is affected (e.g., switch from IgG to IgE) by the level of parasitemia and repeated sensitization to filarial antigens (40)(41)(42).…”
Section: Resultsmentioning
confidence: 99%
“…The larvae mature within several months into lymphaticdwelling adult parasites which release microfilariae (mf) that can be detected in the bloodstream. The level of blood-borne mf is crucial to humoral immune reactions to filarial antigens, ranging from an apparent lack of lymphocyte proliferative responsiveness to a marked degree of lymphoid reactivity and high levels of serum anti-mf antibodies (2)(3)(4). These differences in immune reactivity correlate, in general, with the level of microfilaremia in the human host (5,6 (7).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, both down-regulation by IL-10 and/or TGF-␤ (4 -7), regulation by Th3 or Tr1 cells (3), and changes in the balance of type 1 and type 2 CD4 ϩ cells (4,8) have each been implicated as important mechanisms underlying the filaria-specific down-regulated state. Indeed, Ͼ2 decades ago it was demonstrated that patently infected (microfilaria-positive (Mf ϩ ) 2 ) patients had demonstrable Ag-specific suppressor T cells (9) as well as non-T cell-derived suppressor factors (10). More recently, it has been shown that most, but not all, (11) of this modulating activity is a consequence of the interaction between the microfilarial stage of the parasite (12) and the host cellular immune system, some of which may occur neonatally (13-18).…”
Section: Ctla-4 In Filarial Infectionsmentioning
confidence: 99%